Development of a Single-Borehole Radar for Well Logging - Tingjun Li; Haining Yang; Qing Zhao; Zheng-ou Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
An impulse-based single-borehole radar prototype has been developed for well logging. The borehole radar is comprised of subsurface sonde and surface equipment. An armored 7-conductor well logging cable is used to connect subsurface sonde and surface equipment which is well compatible with the other well logging instruments. The performance experiments of the prototype have been conducted in a test field. The results show that the prototype system is capable of detecting the target which is 8 meters away from the borehole. This radar prototype has been employed in a real oil field well with a depth of about 1600 meters. Compared with conventional resistivity well logging tools, the prototype system provides comprehensive well-bore formation analysis information. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1629